Pengembangan Kurikulum Pendidikan Agama Islam Muslim Minoritas: Pesantren Nurul Yaqin Papua Barat - Wekke, Ismail Suardi (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2013)
Since the founding of Indonesia as a nation, madrasah already contribute to education. This history reflcts madrasah to accelerate people need on education. After long time, madrasah not only stimulate muslim society in education but also at large fild of life. Therefore, this paper explores how the process in madrasah to enhance curriculum. In addition, the study will focus how the administrator of madrasah activate curriculum to extend theenvironment in minority muslim. This study was conducted in qualitative approach. To step up the process of analysis, case study was implemented. During data collection, in-depth interview and non-participant observation were employed. Interview guidelines and observation sheet were carried out to direct the study. Research fidings shows that madrasah in minority muslim, in this study is Pesantren Nurul Yaqin, formulates some programs and activities to develop the madrasah curriculum. Some programs werepracticed to accumulate information from parents, practitioner, and decision maker. There are several processes to enlarge participation and invite people to contribute to the learning material in curriculum. The institution on multiethnic and multicultural society has challenge to synchronize aspiration form different side. On this opportunity to contribute, madrasah accelerate its curriculum in expanding this environment condition. Finally, this research conclude that madrasah in minority muslim on curriculum advancement has chance to encourage students competency that differ from other majority muslim.Keywords: curriculum, enhancement, minority, society